STUDY AND DEVELOPMENT OF EARLY CHILDHOOD EDUCATIONAL LEARNING USING INTERACTIVE STRATEGY BASED ON 2D-ANIMATION - Sarasvathi, Nahalingham; Samia, Bukhari; Mohana, Muniandy (INTI International University, 2018)
The aim of the project reflects on the usage of interactive techniques based on 2D-animation. Early childhood learning ages are of 0 to 8 but this project its primarily focused on the educational aspect for the ages of 4 to 5. The analysis is to prove that early introduction of technology can result in positive aspects of learning and growth factors. It is also to instigate that the use of animation in learning can mold a tender aged growing mind in ways that eludes the tedious and traditional methods of grasping knowledge. In addition, it is to prove that this interactive study can also make the user not know whether they are learning but will cause them to indirectly master skills that will have auspicious results in the long run. The animated learning consists of basic preschool knowledge but manipulated to be interactive to keep the user engaged. Changing the education system by reducing paper-based methods with technology will have the mind stretched positively and in ways that will cause it to redefine its original dimensions which will thoroughly be tested through simplified testing methods.